2017
DOI: 10.18520/cs/v112/i05/989-995
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Nitrous Oxide Emission from <i>Kharif</i> Rice Field as Influenced by Nutrients and Moisture Regimes in New Alluvial Agroclimatic Region of West Bengal

Abstract: INCREASING population and demand for food are placing unprecedented pressure on agriculture and natural resources 1,2 . Agriculture is estimated to account for 10-12% of anthropogenic emissions of greenhouse gases (GHGs) worldwide, including 60% of global nitrous oxide (N 2 O) emissions and 50% of methane (CH 4 ) emissions 3 . Rice paddies are considered one of the most important sources of atmospheric CH 4 , but they also emit N 2 O and the intensity of emissions is related to the nitrogen (N) fertilizer appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that the application of N fertilizers in soil is not totally consumed by the crop; consequently, it is more vital to enhance fertilizer usage efficiency, which can significantly reduce N 2 O emissions [8]. A potential technique for reducing N 2 O emissions is to reduce the amount of N input into the soil [32]. This is due to lesser N input in soil causing competition between plants and soil microorganisms, which favors soil N uptake by plants, resulting in lower N 2 O emission than with high N fertilizer application.…”
Section: Altering Fertilizer Dose and Matching N Supply With Crop Demandmentioning
confidence: 99%
“…It has been reported that the application of N fertilizers in soil is not totally consumed by the crop; consequently, it is more vital to enhance fertilizer usage efficiency, which can significantly reduce N 2 O emissions [8]. A potential technique for reducing N 2 O emissions is to reduce the amount of N input into the soil [32]. This is due to lesser N input in soil causing competition between plants and soil microorganisms, which favors soil N uptake by plants, resulting in lower N 2 O emission than with high N fertilizer application.…”
Section: Altering Fertilizer Dose and Matching N Supply With Crop Demandmentioning
confidence: 99%